Paradigms for fast parallel approximability / Josep Diaz...[et al.] - Diaz, Josep
This is a survey of the basic techniques for approximating combinatorial problems using parallel algorithms. Its core is a collection of techniques that can be used to provide parallel approximations for a wide range of problems. This is an up-to-date reference for graduate students and researchers in algorithmics.